An Integrated Geophysical Approach to Track Magma Intrusion: The 2018 Christmas Eve Eruption at Mount Etna - F. Cannavo'; M. Sciotto; A. Cannata; G. Di Grazia (Geophysical Research Letters)
Abstract On 24 December 2018, a violent eruption started at Mount Etna from a fissure on the southeastern flank. The intrusive phenomenon, accompanied by intense Strombolian and lava fountain activity, an ash‐rich plume, and lava flows, was marked by significant ground deformation and seismicity. In this work, we show how an integrated investigation combining high‐rate GPS data, volcano‐tectonic earthquakes, volcanic tremor, infrasound tremor, and infrasound events allows tracking the magma intrusion phenomenon spatially and temporally with unprecedented resolution. Moreover, it enabled showing how the central magma column lowered as a response to the flank eruption and to constrain the zone of interaction between the dike and the central plumbing system at a depth of 2–4 km below sea level. This is important for understanding flank and summit interaction, suggesting that explosive summit activity may in some cases be driven by lateral dike intrusions.